South Asian Integration Prospects and Lessons from East Asia - Ramesh Chandra; Rajiv Kumar (Indian Council for Research on International Economic Relations (ICRIER), 2008)
In the context of the low levels of regional cooperation among South Asian countries when compared with the successful results from cooperation in East Asia (consisting of South East and East Asian countries), the objective of this paper is first to assess the prospects of cooperation among South Asian economies and then to draw lessons from East Asian regional experiments for South Asian regionalism for the betterment of these prospects. The main argument of the paper is that South Asia should adopt a twin-track approach: better integration within itself and better integration with rest of the world particularly East Asia. Both tracks would complement and supplement each other ensuring a greater chance of success.
Keywords: F15; F33; F36; O19; 330; South Asian integration prospects; Lessons from East Asian regionalism; Open regionalism; Asian development; Regionale Wirtschaftsintegration; Ostasien; Lernen; Internationale Wirtschaftsbeziehungen; Südasien